Influence of NMDA and non-NMDA antagonists on acute and inflammatory pain in the trigeminal territory: a placebo control study Influência dos antagonistas dos receptores NMDA e não-NMDA sobre a dor aguda e inflamatória ao nível do território do trigêmeo: um estudo placebo controlado - Elcio Juliato Piovesan; Vitor Randunz; Marco Utiumi; Marcos Cristiano Lange; Pedro André Kowacs; Rogério Andrade Mulinari; Michael Oshinsky; Maria Vital; Adriana Sereniki; Artur Furlaneto Fernandes; Lucas Leite e Silva; Lineu César Werneck (Arquivos de Neuro-Psiquiatria)
NMDA and non-NMDA receptors are involved in spinal transmission of nociceptive information in physiological and pathological conditions. Our objective was to study the influence of NMDA and non-NMDA receptor antagonists on pain control in the trigeminal system using a formalin-induced orofacial pain model. Motor performance was also evaluated. Male Rattus norvegicus were pre-treated with topiramate (T) (n=8), memantine (M) (n=8), divalproex (D) (n=8) or isotonic saline solution (ISS) (n=10) intraperitoneally 30 minutes before the formalin test. Formalin 2.5% was injected into the right upper lip (V2 branch) and induced two phases: phase I (early or neurogenic) (0-3 min) and phase II (late or inflammatory) (12-30 min). For motor behavior performance we used the open-field test and measured latency to movement onset, locomotion and rearing frequencies, and immobility time. Pre-treatment of animals with M and D only attenuated nociceptive formalin behavior for phase II. T increased locomotion and rearing frequencies and reduced immobility time. Treatment with M increased immobility time and with D reduced locomotion frequency. Our results showed that the NMDA antagonist (M) is more potent than the non-NMDA antagonists (D and T) in the control of pain in the inflammatory phase. The non-NMDA topiramate improved motor performance more than did D and M, probably because T has more anxiolytic properties. Receptores NMDA e não-NMDA estão envolvidos na transmissão das informações nociceptivas em condições fisiológicas e patológicas. Com o objetivo de estudar a influência dos antagonistas dos receptores NMDA e não-NMDA sobre o controle de dor no sistema trigeminal utilizamos modelo de dor orofacial induzida pela formalina. Testes de desempenho motor foram também avaliados. Ratos machos da espécie Rattus norvegicus foram tratados com topiramato (T) (n=8), memantina (M) (n=8), divalproato de sódio (D) (n=8) ou solução salina isotônica (SSI) (n=10), por via intraperitoneal, 30 minutos antes dos testes com a formalina. Formalina 2.5% foram injetadas na região do lábio superior dos animais (segundo ramo do trigêmeo) induzindo comportamento em duas fases distintas: fase I (precoce ou neurogênica) (0-3 min ) e fase II (tardia ou inflamatória) (12-30 min). Para avaliação da atividade motora utilizou-se o teste do campo aberto mensurando-se a latência para o início dos movimentos, número de casas andadas, freqüência de levantamentos e tempo de imobilidade. Animais pré-tratados com M e D atenuaram a fase inflamatória do teste da formalina. O T aumenta o número de casas andadas, freqüência de levantamentos e reduz o tempo de imobilidade. Nossos resultados mostram que o antagonista NMDA é mais potente do que os antagonistas não-NMDA para o controle da fase inflamatória da dor. O topiramato entretanto aumenta a atividade motora provavelmente porque apresente propriedades ansiolíticas.